Addendum to 2‐Butoxyethanol (Ethylene glycol monobutyl ether) [BAT Value Documentation, 2016]. Issue 4 (19th October 2018) - Göen, T.; Rettenmeier, A.W.; Drexler, H.; Hartwig, A.; ,
Abstract: In 2015 the German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated the biological tolerance value at the work place (BAT value) for 2‐butoxyethanol (ethylene glycol monobutyl ether) [CAS No. 111‐76‐2 ], considering butoxyacetic acid in urine to characterise the internal exposure. The main systemic adverse effects of 2‐butoxyethanol are on the haematopoietic system (haemolytic effects), followed by possible teratogenic and testicular effects. 2‐Butoxyethanol was classified in category 4 for carcinogenic substances, which enables the evaluation of a health based exposure limit. It can easily pass through the skin, so biological monitoring is necessary for a valid individual risk assessment. A considerable part of the absorbed 2‐butoxyethanol is excreted in form of the glutamine conjugate of butoxyacetic acid, i.e. N‐butoxyacetyl glutamine. The relative amount of this conjugate in the total excretion of butoxyacetic acid varied considerably intra‐ and inter‐individually depending on the exposure levels and possibly on enzyme polymorphisms. On average half of the total butoxyacetic acid is excreted in the form of the glutamine conjugate (factor 2). Various studies indicate that at high exposure levels the capacity of the conjugate reaction is exceeded and lower conjugated amounts appear. Due to the high variability of conjugated amounts of the butoxyacetic acid and the limitation of conjugated amounts at high exposure levels the previous BAT value for free 2‐butoxyacetic acid is converted with a factor of 1.5 to the total amounts of 2‐butoxyacetic acid. Additionally, the impact of diuresis is considered by the relation to the creatinine concentration. Therefore, a BAT value for the total butoxyacetic acid excretion of 150 mg butoxyacetic acid (after hydrolysis)/g creatinine was established. Sampling should be performed at the end of exposure and shift, respectively, after several previous shifts. This BAT value applies also for combined exposure to 2‐butoxyethanol and 2‐butoxyethylacetate.